Are live lectures a discontinued model? A survey on the influence of synchronous online lecturing on the perception of teaching and assessment outcome - Osten, Jannik; Behrens, Victoria; Behrens, Sadie; Herrler, Andreas; Clarner, Tim (GMS Journal for Medical Education, 2023)
Objectives: In the early phase of their studies, students are confronted with a number of teaching and learning methods they are usually not familiar with. Beyond, learning in a university environment requires a high degree of self-organization. Thus, the transition from learning in a school environment to university can be challenging for students and associated with adjustment difficulties. We hypothesized that synchronous online lecturing might be able to serve as a thematic superstructure and a curricular guide that can positively influence course perception, motivation and exam outcome.Methods: We investigated this hypothesis in a retrospective approach by comparing results from histology exams (2020 n=411, 2021 n= 423) and questionnaires for course evaluation received from medical and dentistry second semester students of the RWTH Aachen University, Germany, in 2020 (n=113 questionnaire participants) and 2021 (n=106 questionnaire participants). While in 2020, due to the Corona Pandemic, no synchronous online lectures were held, these were reintroduced in 2021. Results: Our results show several differences in between the two study cohorts. Most important findings include a significantly (p<0.001) lower number of students that failed to pass or withdrew from the exam in 2021, an increased motivation to deal with the learning content (p<0.001) and a higher perceived quality of the study materials (p<0.001) in 2021.Conclusion: Our study indicates that synchronous online lectures can be an important tool to help students to accustom to new learning environments and to structure private study. Further studies will now have to show whether live (online) lectures can have the same significance during clinical training.